The selective proximal vagotomy by the method of chemical denervation in the treatment of patients with perforating pyloroduodenal ulcers - O. A. Krasnov; D. N. Grekov; V. I. Podoluzhnyi; O. V. Oorzhak; V. V. Pavlenko (Бюллетень сибирской медицины)
The aim of the study was to optimize the technical conditions of the selective proximal vagotomy in patients with perforating pyloroduodenal ulcers by the chemical denervation method. The diffusion method was applied, which includes the study of the proteolys of the top parts of a digestive tract by the Gorshkovs’ method (Gorshkov V.A., 1988). The results of treatment of 88 (the control group) and 82 (the basic group) patients with perforating pyloroduodenal ulcers (PPDU) for the period 1990—2002 are presented. The patients were subjected to the combination of suture plication and selective proximal vagotomy (SPV) by the method of skeleting of small curvature of stomach and the method of the chemical denervation. The results of treatment in the nearest postoperative period and in the long terms up to five years are analyzed. The stable decrease of the acidic and proteolytical activity (APA) (proteolys (419,0 ± 23,2) g/m2 × 24–1, concentration of the hydrochloric acid (18,4 ± 2,4) mmol/l) of the stomach body in the both groups of patients was established, accompanied by the low percentage of relapse of a duodenal ulcer, which was uncertainly higher in the basic group (4,3 and 7,3% respectively). Simplicity and availability of the chemical denervation method and its efficiency allow it to be recommended for the wide application.